Accelerated Testing of High Power Transistors for Long Operation when Solving Problems of Prediction of their Reliability by the Method of Imitation Simulation - V. O. Kaziuchyts; E. V. Kalita; S. M. Borovikov; A. I. Berasnevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
When evaluating the individual reliability of semiconductor devices by gradual failures for a given operating time, the value of the electrical parameter of a particular instance for this operating time is predicted using the simulation method. To obtain a prediction of an electrical parameter, it is necessary to have a simulation model in the form of a function of the relationship between a given operating time and the level of simulation impact. The simulation model is obtained with the help of preliminary studies (training experiment) of a training sample of semiconductor devices of the type of interest with the volume of approximately 50 ... 100 copies. The application of the model is reduced to the calculation of the level of simulation impact corresponding to a given operating time. The result of measuring the electrical parameter at the calculated level of the imitation impact in a new specimen of the same type that did not take part in the training experiment should be considered as a prediction of this parameter for a given operating time. An integral part of the preliminary research to obtain a simulation model is the testing of semiconductor devices of the training set for a long operating time, which can be tens of thousands of hours, which necessitates planning and conducting accelerated tests. The article substantiates the conditions for conducting accelerated forced tests in relation to high-power bipolar transistors of the KT872A type. The increased temperature and the reverse voltage applied to the collector junction of the transistors are chosen as factors accelerating the tests. The test acceleration coefficient is calculated relative to the operating mode of the transistors. Based on the results of the accelerated tests for the electrical parameter (collector-emitter saturation voltage), a mathematical model was obtained in the form of a dependence of its average value on the operating time. The presence of this model is necessary to determine the function of recalculating the given operating time of transistors to the value of the simulation impact.